The Influence of The Corporate Governance Perception Index on The Share Price of PT. Bank Rakyat Indonesia, Tbk for The Period of 2015-2023 - Asyifa Sulistiani, Nicky; Noor, Saad (International Research & Development for Human Beings (IRDH), 2024)
This study investigates the impact of the Corporate Governance Perception Index (GCPI) on the stock price of PT. Bank Rakyat Indonesia, Tbk, from 2015 to 2023. Effective corporate governance (GCG) is crucial for the long-term profitability and sustainability of a firm, particularly in the banking industry, which plays a critical role in the economy. The Corporate Governance Perception Index (CGPI) is utilized in Indonesia to assess the level of GCG implementation and gauge its quality. This study employs a quantitative approach to examine the impact of CGPI on the stock price of the company within the time frame of 2015-2023, utilizing data extracted from financial statements and annual reports. The analysis conducted using SPSS indicates a robust correlation between CGPI (Consumer Goods Price Index) and stock prices. The descriptive analysis and normality test results indicated that the residual data exhibited a normal distribution, without any indications of multicollinearity or heteroscedasticity. The association between the Consumer Goods Price Index (CGPI) and stock price is statistically significant. A regression model indicates that for each unit increase in CGPI, the stock price increases by 0.220 units. The coefficient of determination, which is 0.728 in this case, signifies that this model can account for 72.8% of the fluctuations in stock prices. The partial test of T indicates a statistically significant impact of CGPI on stock prices, with a significance level below 5%. This study highlights the significance of corporate governance (GCG) in exerting an influence on stock prices. It suggests conducting additional research that incorporates other variables, such as macroeconomic conditions or government regulations, in order to evaluate the reliability of the findings. Furthermore, the study proposes exploring different sectors to assess the consistency of the results.